2017
DOI: 10.1016/j.sajb.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypical and physiological study of near-isogenic durum wheat lines under contrasting water regimes

Abstract: Irrigation treatments involving three different water regimes were carried out in a controlled environment on eight near-isogenic durum wheat lines that differed in a major yield-related QTL region (QYld.idw-3B) in order to assess the relationship between morphophysiological traits, antioxidant enzyme activities, polyamine contents and drought tolerance.Drought stress, simulated under a rain-out shelter, negatively affected the performance of the isogenic lines, leading to significant reductions in seed yield,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…In the present study, the AMMI and pooled-based analysis of variance showed a high and significant amount of variation among 13 wheat genotypes based on eight different traits. The high level of genetic variation, which is significantly observed in the present as well as in previously published studies, using near-isogenic lines confirmed the availability of a golden opportunity to employ the near-isogenic population for wheat improvement programmes with a special focus on GPC and yield ( Bányai et al, 2017 ; Kokhmetova et al, 2017 ). In this study, we particularly focused on yield and GPC for the following reasons: 1) wheat grain yield is very important since it is a stable source of food for the world’s population 2) GPC is an important determinant of food quality 3) combining higher grain yield and higher GPC in an individual wheat variety is considered as an important determinant of food and nutritional security in the world.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, the AMMI and pooled-based analysis of variance showed a high and significant amount of variation among 13 wheat genotypes based on eight different traits. The high level of genetic variation, which is significantly observed in the present as well as in previously published studies, using near-isogenic lines confirmed the availability of a golden opportunity to employ the near-isogenic population for wheat improvement programmes with a special focus on GPC and yield ( Bányai et al, 2017 ; Kokhmetova et al, 2017 ). In this study, we particularly focused on yield and GPC for the following reasons: 1) wheat grain yield is very important since it is a stable source of food for the world’s population 2) GPC is an important determinant of food quality 3) combining higher grain yield and higher GPC in an individual wheat variety is considered as an important determinant of food and nutritional security in the world.…”
Section: Discussionsupporting
confidence: 86%
“…The NIL pairs were obtained by MAS (Marker-assisted selection), selecting pairs differing only for the 3BS QTL (the NILs were all fixed for “Kofa KK allele” on chromosome 2B). When the QYld.idw-3B region on chromosome 3B was “Kofa KK” (KK2BLKK3BS), the NILs were coded as ++ (“NIL1++”, “NIL2++”, “NIL3++”, ”NIL4++”), and when the allele was “Svevo SS” (KK2BLSS3BS), they were coded as −− (”NIL1—“, ”NIL2−−”, ”NIL3−−”, ”NIL4−−”) [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Creating a suitable population for examining QTL effects is a complex task because differential gene expression is caused not only by the trait of interest but also by the variation present in the genetic background [ 38 ]. One solution for establishing the functional association between the level of gene expression and a given trait is the use of a set of near-isogenic lines (NILs), which are genetically similar except for a single gene, marker or trait [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our observations, Feng et al (2011) also reported that higher levels of Spd and Spm were closely associated with higher kernel set and better seed development in maize and greater grain filling rate in rice (Yang et al 2008). Yield-related parameters have also reported to be in a significant positive relationship with the PA contents of durum wheat flag leaves (Bányai et al 2017).…”
Section: Discussionmentioning
confidence: 98%